Prognostic Implications of Dual Platelet Reactivity Testing in Acute Coronary Syndrome - de Carvalho, Leonardo P.; Fong, Alan; Troughton, Richard; Yan, Bryan P.; Chin, Chee-Tang; Poh, Sock-Cheng; Mejin, Melissa; Huang, Nancy; Seneviratna, Aruni; Lee, Chi-Hang; Low, Adrian F.; Tan, Huay-Cheem; Chan, Siew-Pang; Frampton, Christopher; Richards, A. Mark; Chan, Mark Y. (Thrombosis and Haemostasis, 2018)
Studies on platelet reactivity (PR) testing commonly test PR only after percutaneous coronary intervention (PCI) has been performed. There are few data on pre- and post-PCI testing. Data on simultaneous testing of aspirin and adenosine diphosphate antagonist response are conflicting. We investigated the prognostic value of combined serial assessments of high on-aspirin PR (HASPR) and high on-adenosine diphosphate receptor antagonist PR (HADPR) in patients with acute coronary syndrome (ACS). HASPR and HADPR were assessed in 928 ACS patients before (initial test) and 24 hours after (final test) coronary angiography, with or without revascularization. Patients with HASPR on the initial test, compared with those without, had significantly higher intraprocedural thrombotic events (IPTE) (8.6 vs. 1.2%, p ≤ 0.001) and higher 30-day major adverse cardiovascular and cerebrovascular events (MACCE; 5.2 vs. 2.3%, p = 0.05), but not 12-month MACCE (13.0 vs. 15.1%, p = 0.50). Patients with initial HADPR, compared with those without, had significantly higher IPTE (4.4 vs. 0.9%, p = 0.004), but not 30-day (3.5 vs. 2.3%, p = 0.32) or 12-month MACCE (14.0 vs. 12.5%, p = 0.54). The c-statistic of the Global Registry of Acute Coronary Events (GRACE) score alone, GRACE score + ASPR test and GRACE score + ADPR test for discriminating 30-day MACCE was 0.649, 0.803 and 0.757, respectively. Final ADPR was associated with 30-day MACCE among patients with intermediate-to-high GRACE score (adjusted odds ratio [OR]: 4.50, 95% confidence interval [CI]: 1.14–17.66), but not low GRACE score (adjusted OR: 1.19, 95% CI: 0.13–10.79). In conclusion, both HASPR and HADPR predict ischaemic events in ACS. This predictive utility is time-dependent and risk-dependent.
Keywords: antiplatelet therapy; acute coronary syndrome; thrombosis